تقييم تطبيق النظام المحاسبي المالي في ظل بيئة المحاسبة الجزائرية -رأي مهني - بن حركو, غنية (جامعة الوادي - University of Eloued, 2022)
يهدف هذا البحث إلى معرفة واقع تطبيق النظام المحاسبي المالي في ظل تحديات البيئة المحاسبية الجزائرية، وبغية الحصول على البيانات اللازمة والأكثر ارتباطا بالواقع تم الاستعانة باستبيان موجه إلى عينة من الفاعلين في مجال المحاسبة، وخلصت الدراسة إلى أن الجزائر قامت بإصلاح نظامها المحاسبي بهدف تقريب الممارسة المحلية إلى الممارسة الدولية بتطبيق نظام محاسبي مالي مستوحى من معايير المحاسبة الدولية، إلا أنه لم يحقق الأهداف المرجوة منه بعد سنوات من التطبيق، وهذا يرجع إلى الصعوبات الموجودة في البيئة المحاسبية الجزائرية والتي تحول دون التطبيق السليم للنظام المحاسبي المالي والتي تتمثل في ضعف التأهيل الأكاديمي، إضافة إلى جمود القواعد الجبائية This research aims to determine the extent to which the accounting and financial system is applied, especially in the context of Algeria. In order to do so, a survey has been distributed on a sample of the main actors in the field including academics, practitioners and tax administration executives. The collected data has been processed and analyzed using a pallet of statistical methods. Results show that Algeria has already undertaken the reform of its accounting and financial system in accordance with the directives of the IAS. However, after years, the objectives of this reform have not yet been reached. This is mainly due to the multiple barriers that characterize the accounting environment in Algeria, such as weak qualifications of the practitioners, out dated fiscal laws
مقال
Keywords: تقييم، النظام المحاسبي المالي، البيئة المحاسبية الجزائرية.; Evaluating, accounting and financial system, accounting environment in Algeri